Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Du, Juan; Liu, Yang; Pei, Tao; Li, Anzhang; Deng, Ming-Rong; Zhu, Honghui (Archives of microbiology, 2022)
A novel aerobic, yellow, and rod-shaped bacterial isolate, designated as 1Y8A T , was isolated from aquaculture water sampled in Jiangmen, Guangdong province, P. R. China. Here, the taxonomic position of strain 1Y8A T was conducted based on phenotypic, genomic, and chemotaxonomic characteristics. Strain 1Y8A T was observed to grow at 10–37 °C (optimum 28 °C), at pH 6.0–9.0 (optimum 7.0) and in 0–2% NaCl (optimum 1%, w/v). The 16S rRNA gene-based analysis showed that strain 1Y8A T was closely related to “ Flavobacterium sasangense ” YC6274 T (99.3%), Flavobacterium aquaticum JC164 T (98.4%), Flavobacterium cucumis R2A45-3 T (98.0%), Flavobacterium celericrescens TWA-26 T (98.0%), and Flavobacterium cheniae NJ-26 T (97.2%). The digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) values between strain 1Y8A T and reference strains above were far below the recognized thresholds of 70% dDDH and 95–96% ANI for species definition, implying that the strain represents a novel genospecies. The phylogenomic analysis indicated that strain 1Y8A T formed an independent branch distinct from known species. The major cellular fatty acids of strain 1Y8A T were iso-C 15:0 , iso-C 15:1 G and C 15:0 ; the polar lipids comprised phosphatidylethanolamine, glycolipid, and two lipids; the respiratory quinone was MK-6. The G + C content of genomic DNA was 32.5%. Based on the genotypic and phenotypic characteristics such as the utilization of D-glucose and casein hydrolysis, strain 1Y8A T is concluded to represent a novel species of the genus Flavobacterium , for which the name Flavobacterium proteolyticum sp. nov. is proposed. The type strain of the species is 1Y8A T (= GDMCC 1.1933 T = KACC 22081 T ).